Thermoelectric effect of wear of alloy bearing. (September 2019) - Zhu, Jun; Gao, Hong-liang; Pi, Da-neng; Xie, Zhong-qing; Mei, Lei
Abstract: In this paper, the thermoelectric effect of wear of alloy bearing is analyzed, and the change characteristics of thermoelectric signals of different types and different working conditions of alloy bearing are measured and analyzed. The results show that the thermoelectric signals of the alloy bearing start from scratch, and there are temperature difference potential and contact potential; the thermoelectric signals of the alloy bearing change in a good repeatability during steady-state operation, and the peak value of the thermoelectric signals of the alloy bearing corresponds to the number of cylinders in a working cycle; the mean, peak value of the thermoelectric signals correspond to the thickness of the oil film. The relationship among degree, temperature difference potential and contact potential can be used to judge accumulative wear and instantaneous wear of alloy bearing in real time, which proves the feasibility of on-line wear monitoring of alloy bearing based on thermoelectric effect. Highlights: The experimental results show that the thermoelectric signal increases from zero at the start of the diesel engine, and there exist the temperature difference potential and the contact potential. The thermoelectric signal of sliding main bearing in steady state is well reproducible, and the peak number of the thermoelectric signal in a working cycle equals to the number of cylinders. The cumulative wear and instantaneous wear of sliding main bearings can be judged in real time by means of the characteristics that the mean value of thermoelectric signal increases with the increase of temperature difference potential and the peak value increases with the increase of contact potential.